A tailor-made learning environment workspace for generation y graduates using product service system concept. (November 2019) - Akmal, S; Hambali, R H; Maidin, S; Shahmir, M R; Abdul Shukor, S A
Abstract: This paper presents a workspace design of a tailor-made learning environment for students using the product-service systems (PSS) concept. Existing research regarding workspace design focuses on the design of the interior of classrooms to ensure that the learning process proceeds with minimum stress and maximum effectiveness. None of the current research had discussed the workspace outside of the classroom. Therefore, the main objective of this study is to propose a learning environment workspace in which students can gather, study, relax, socialize, eat, and work during class gaps. For this purpose, a questionnaire was distributed to identify the behavior of the users to generate a list of requirements in the development of the learning workspace. This paper focused on students at the Engineering Faculty and the learning environment workspace was called the OneForAll Center. Out of 10 functions of the proposed OneForAll Center, only four functions had the highest priority: a space to use a laptop and internet connection, a television, a vending machine and a printing section. The OneForAll Center has been illustrated in a 3D model and shown to the students, in which most of them agreed with the proposed services and facilities such as a space to use the laptop and internet connection and a printing section with a printing service. The OneForAll Center has been identified as a solution to improve learning outside the classroom, specifically to the provision of services to students.